KALIBRASI TES CAMPURAN DIKOTOMUS 2PLM DAN POLITOMUS GRM MENGGUNAKAN PROSEDUR GRM DAN GPCM - Samritin Samritin (JEC (Jurnal Edukasi Cendekia), 2018)
Item parameter estimation is an important step in test development. Estimation of test parameters must pay attention to the suitability of the response characteristics with the calibration procedure to be used. This study has simulated mixed test response data of 35 dichotomous items of 2PLM with 5 polytomous items of GRM. Response data was generated using a sample size of 1500 examinees. Response data were analyzed descriptively from the aspect of correlation coefficient, root mean square difference (RMSD), mean absolute difference (MAD), variance, and bias. The results of this study indicate that the estimation of the slope and threshold parameters of the dichotomous test model 2 logistic parameters using GRM calibration produces correlation coefficients, RMSD, MAD, variance, and estimation bias that are almost the same as those of the GPCM calibration; parameter estimation of the slope and threshold of the GRM model polytomous test using GRM calibration produces a smaller correlation coefficient, RMSD, MAD, variance, and estimation bias compared to the GPCM calibration results; and estimation of the slop parameters and threshold of the mixed dichotomous 2 parameter logistic model (2PLM) test and the GRM polytomous test calibrated using the GRM procedure produced a higher correlation coefficient but had lower RMSD, MAD, variance, and bias compared to the results of calibration using the GPCM procedure. Based on the results of data analysis, this study concluded that the parameter estimation of the 2PLM dichotomous and polytomous GRM mixed test is more precise when calibrated using the GRM procedure.